Arun Kolatkarchya Kavita: Modernity and Stylistics - Aher, Jayashri Balasaheb (Advances in Social Sciences Research Journal, 2026)
Arun Kolatkar, a major poetic voice of Indian poetic scene, a bilingual poet who prolifically composed in Marathi and in English, an important translator of saint poets like Tukaram and Janabai, self- translator of phenomenal potential started writing poetry in the decade of fifties. His first collection of poems in Marathi titled “Arun Kolatkarchya Kavita” came out in 1977. Seventy-three poems have been compiled in this first collection. Out of these, 40-50 poems of first half are extremely complex and elusive. These are the very poems which set up Kolatkar’s image as exceedingly elusive poet in Marathi. Critics and readership of the time made every attempt to understand the ins and outs for the elusiveness of his poems. At the same time Kolatkar proved to be the first modern poet in every sense on the canvas of Marathi Poetry. Linguistically, he is still the most experimental poet in Marathi. The article attempts to study various aspects of modernity and stylistics of the poems in this first collection, in the context of the contemporary literary scene, the readership and the politics of taste of the time of the sixties, which proved instrumental for the cold reception of these really valuable bunch of poems which in several ways could set the tone and trend of Marathi Poetry.